Media technology and society : a history : from the telegraph to the internet - Winston, Brian (London : Routledge, 1998)
Propagating sound at considerable distances. The vital spark and fugitive pictures. Inventions for casting up sums very pretty. The intricate web of trails, this grand system.
Keywords: Mass media; Technological innovations; Mass media -- Technological innovations -- History; Communication -- Technological innovations -- History; Communication -- Social aspects; Mass media -- Social aspects